Copper-containing nanoparticles: Mechanism of antimicrobial effect and application in dentistry-a narrative review - Ma, Xinru; Zhou, Shiyu; Xu, Xiaoling; Du, Qin (Frontiers in Surgery, 2022)
The antimicrobial properties of copper have been known since ancient times. In recent years, with the emergence of antibiotic resistance and the increasing need for reducingto reduce antibiotics’ application, nanoparticles (NPs) with antimicrobial properties have drawn wide attention. Nanotechnology has been gradually used in all aspects of the health care system, including multiple areas of dentistry. Copper-containing NPs may be incorporated or coated on the surface of dental materials, so as to inhibit oral pathogenic microorganisms’ growth and formation of biofilms. This review aims to detail copper-containing NPs’ antimicrobial mechanism,cytotoxic effect and inhibitory effect on oral pathogenic microorganisms. Moreover, their application in dentistry is also discussed.